Detection and Identification of Potentially Harmful Microalgal Species in Doreri Bay, Manokwari, West Papua, Indonesia: A Preliminary Study - Tururaja, Tresia Sonia; Bawole, Roni; Mogea, Rina A.; Murtihapsari, Murtihapsari; Manan, Jemmy; Kusuma, Aradea Bujana; Kolibongso, Duaitd (Marine Science Department Diponegoro University, 2025)
Harmful algal blooms (HABs) frequently exhibit recurring patterns in specific locations and are often associated with significant environmental challenges, such as eutrophication. However, HABs have also been observed in areas with lower levels of eutrophication. This study aimed to detect and identify phytoplankton species responsible for blooms in the waters of Doreri Bay, with a particular focus on potentially harmful species (HABs). It represents the first attempt in this region to identify microalgal species. Field sampling was conducted during the southeast (dry) season of 2023 at nine stations across Doreri Bay. A total of 21 phytoplankton taxa, representing three classes were identified, with 14 taxa (66.7%) being potentially harmful. Phytoplankton cell densities ranged from 2.96 × 10⁴ cells L-1 to 1.22 × 10⁵ cells L-1, with an average density of 2.01 × 10⁴ cells L-1. The community was dominated by Diatoms, including Bacillaria spp., Coscinodiscus spp., and Rhizosolenia spp., and Cyanobacteria, mainly Trichodesmium spp. Two bloom patterns were observed: Cyanobacteria and Dinoflagellates dominated coastal areas, while Diatoms were more abundant in the outer bay. Correlation analysis revealed that temperature, salinity, and dissolved oxygen (DO) were the primary environmental factors driving phytoplankton variability and growth in the shallow coastal waters of Doreri Bay. These findings suggest that the phytoplankton community structure in this region remains stable when environmental gradients stay within the tolerance thresholds of sensitive species. Conversely, potentially harmful algal blooms are likely to develop when these environmental gradients exceed the tolerance levels of more resilient species.